2007
DOI: 10.1243/09544070jauto504
|View full text |Cite
|
Sign up to set email alerts
|

Intake and in-cylinder flowfield modelling of a four-valve diesel engine

Abstract: A three-dimensional unsteady turbulent compressible Navier-Stokes solver, KIVA3V, was utilized in the present study to investigate the intake and in-cylinder flowfield of a four-valve direct injection compression ignition engine. Successful modelling of internal combustion engine configurations is highly dependent upon the generation of a quality grid with the correct boundary conditions. The preprocessor of the KIVA3V computer code, K3PREP, was improved, and a complete grid for a four-valve/cylinder single-cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The TKE for all the models declined linearly after 330°CA. The pattern of TKE which declined linearly not only reported by Payri [42] and Prasad [43] but also by other researchers [47] as well. By comparing the pattern of TKE and the shape of average TKE from 341°CA until 365°CA for various models as illustrated in Figure 5, it can be concluded that an appropriate agreement with the results of other researchers is achieved.…”
Section: In-cylinder Turbulence Kinetic Energy (Tke)supporting
confidence: 70%
“…The TKE for all the models declined linearly after 330°CA. The pattern of TKE which declined linearly not only reported by Payri [42] and Prasad [43] but also by other researchers [47] as well. By comparing the pattern of TKE and the shape of average TKE from 341°CA until 365°CA for various models as illustrated in Figure 5, it can be concluded that an appropriate agreement with the results of other researchers is achieved.…”
Section: In-cylinder Turbulence Kinetic Energy (Tke)supporting
confidence: 70%
“…Tests and simulation methods were often used to study the flow field in the intake port and incylinder of diesel engines (Deqing et al, 2002, Micklow G J,et al,2007, Ma Hongwei,et al,2013, Wang Tianyou,et al,2008, Stiehl, R.,et al,2016.At the same time, the intake port design method of some non diesel engine was also studied (Yuguo, et al,2014, Thangavel et al, 2016 ,at last , the ports were optimized , Son, J. W.,et al,2004. Because the air flow in-cylinder was difficult to experiment research at the same time, the three-dimensional models of four different combined intake ports with spiral and tangential port were established.…”
Section: Introductionmentioning
confidence: 99%
“…Here fuel is injected directly into the main chamber into a deep bowl in piston, within which a highly swirling air has been created during suction and compression stroke. By which rapid mixing between fuel and air has been achieved [1].…”
Section: Introductionmentioning
confidence: 99%